БЎЛАЖАК ЎҚИТУВЧИ - ТАЛАБАЛАР ЖИСМОНИЙ ФАОЛЛИГИНИ ЭРТАЛАБКИ ГИМНАСТИК ВА ЮГУРИШ МАШҚЛАРИ ЁРДАМИДА ОШИРИШ САМАРАДОРЛИГИ - Мамадалиев, Қ.М. (SCIENCE and SOCIETY, 2022)
The purpose the article is to discover physical education and sports health-improving activities in teaching the future teachers, students based on the requirements of physical development of organism and healthy lifestyle. At the same time, the effectiveness of increasing the physical activity of the future - teacher, students with the help of morning gymnastic and running exercises, physical education, sports and wellness activities have been studied to help a great deal in the positive mastering of specialty training.